IDENTIFIKASI KARAKTERISTIK DAN MUTU JAGUNG DI KABUPATEN SIDENRENG RAPPANG - Salfiana, S.TP., M.Si. (UPPM Politeknik Gorontalo, 2022)
Identification of characteristics and quality of corn a case study in Sidenreng Rappang Regency. This research aims to measure or identify quantitatively the character of corn and determine the classification of corn quality. Sampling came from each representative sub-district in Sidenreng Rappang Regency. The samples obtained were 11 (eleven) samples from each sub-district. Physical measurements and aflatoxin testing were carried out on the best samples of the 11 samples. This corn sample is a hybrid maize of Pertiwi-6. The research was carried out by determining broken grains, other colored grains, broken grains, dirt content, determination of water content, physical properties and aflatoxin. The results showed that 81.82% of maize in Sidenreng Rappang Regency had complied with the quality requirements of SNI Maize, while 18.18% of them do not meet the quality standards. The results of 11 samples, there are 9 samples that meet the quality requirements specifications in accordance with SNI Corn SNI 3920:2013, however there are 2 samples that do not belong to the quality class. Characteristics of Hybrid Pertiwi-6 maize growing in Sidenreng Rappang Regency generally have characteristics with a length of 8- 14 mm, a width of 7-8 mm, a weight of 250 (mg/seed), Bulk density 745 (Kg/m3). Aflatoxin levels obtained < 1.0 g/Kg. The aflatoxin levels have met the Indonesian national standards. These results indicate that the quality of corn in Sidenreng Rappang Regency needs to be maintained, but there are still some whose quality needs to be improved in accordance with applicable quality standards.